Leon Botstein Public Lecture - Music in Historical Context - Part 1
Recording of Leon Botstein (President of Bard College, New York, and Music Director, American Symphony Orchestra) giving a public lecture at CEU on April 5, 2001 in Gellner Room. Among the highlights in his talk on "Music in Its Historical Context" were contrasting historical and contemporary experiences: for example, intense modern familiarity via the prism of specific interpretations, "Humphrey Bogart moments" and the change in the music playing abilities of the audiences today as opposed to the "elite amateurism" existing in the 1830s. The lecture is then followed by a commentary of musicologist Judit Frigyesi ( Bar-Ilan University, Collegium Budapest) who elaborated on the problem of music by drawing on the example of Bartók and his modernist milieu in turn-of the-century in Budapest.